Alterations of consciousness : an empirical analysis for social scientists - Barušs, Imants, 1952- (American Psychological Association, 2020)
"Now in a second edition, this pathbreaking investigation into the nature of cognitive reality explores various manifestations of consciousness, including more familiar states such as sleeping and dreaming, as well as hypnosis, trance, dissociation, and near-death experiences. Throughout the work, Barušs brings to bear significant new neuroscientific evidence supporting the occurrence of these phenomena and their nature and purpose. Other major updates include the latest findings in sleep research, therapeutic discoveries related to psychedelics, empirical research into transcendent states, and developments in the study of anomalous phenomena such as purported alien abduction and UFOs. developments in the study of alien abduction and UFOs, and a new conclusion discussing an exosomatic theory of consciousness that can account for the findings in the text. Students and other readers of this engaging text will sharpen their critical thinking skills and gain an enriched understanding of consciousness, reality, and the scientific endeavor"--